Vestígios da tradição dos ofícios na indústria: o ensino da encadernação no Brasil até as séries metódicas do SENAI, nos anos 50 - Brito, Fernanda Kelly Silva de (2015)
The presence of evidence of bookbinding craft tradition in industrial teaching methodology of the years 50 confirms our hypothesis that there is a stay of actions and practices that show us the continuity of this tradition, even with its fragmentation proposed by the Taylor s vision. Thus, this dissertation analyzes the methodology used by SENAI expressed in methodical series and its application to binding course and books used to teach it. The survey was conducted presenting the binding context from XVth century, with the typographic workshops, after the establishment of hierarchies in the craft guilds and further research was carried out on the binding offices in Brazil and institutions that ministered. We analyzed how was this teaching in Brazil during the industry to the creation of the SENAI, through published works in partnership with the Ministry of Education and Health Issues and the Brazilian American Commission on Industrial Education. At the end of our research shows the analysis of a task, from the book "Binding Course", one of the works published by SENAI, for demonstration as applied methodical series to the craft of bookbinding and references used in its making, checking the evidence on the tradition of bookbinding craft in the context of industrial training